2015
DOI: 10.7843/kgs.2015.31.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Change of Slope Stability due to Slope Inclination and Surface Conditions

Abstract: Slope stability is affected by duration of precipitation, probable rainfall intensity, unsaturated soil property, and soil strength. The recent analyses of slope stability tend to include unsaturated analysis based on infiltration properties of soil, while researches of unsaturated soil slope tend to include the analysis of deformation and stress distribution of soil over time. However, infiltration property of unsaturated soil slope depends not only on intensity or duration of precipitation, but also on relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In recent years, many experts have analyzed the causes of slope instability [5] and destruction [6] through extensive research and found that the main causes of slope damage are mostly rainfall [7], floods [8], and wind action [9] that eroded the soil of the slope, cracked the subgrade slope, reduced the resistance of the subgrade slope to external forces, and eventually caused the slope to collapse and lose stability. Against the various causes of subgrade slope instability and destruction, many slope protection technologies and methods have been proposed after a large number of engineering tests, which are basically divided into engineering protection technology and plant protection technology.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many experts have analyzed the causes of slope instability [5] and destruction [6] through extensive research and found that the main causes of slope damage are mostly rainfall [7], floods [8], and wind action [9] that eroded the soil of the slope, cracked the subgrade slope, reduced the resistance of the subgrade slope to external forces, and eventually caused the slope to collapse and lose stability. Against the various causes of subgrade slope instability and destruction, many slope protection technologies and methods have been proposed after a large number of engineering tests, which are basically divided into engineering protection technology and plant protection technology.…”
Section: Introductionmentioning
confidence: 99%